δ(M) - Supplemented Modules - Yaseen, Sahira M; Salman, Zainab T (Al-Nahrain Journal of Science, 2011)
Let R be an associative ring with identity and M a non-zero unitary R-module. We introduce the concept of δ(M)– Supplement Submodule that if A,B≤M and M=A+B then B is called δ(M) – supplement of A if A∩B≤ δ(B) We give some properties of this kind of module